2011
DOI: 10.1128/jb.05359-11
|View full text |Cite
|
Sign up to set email alerts
|

Negative Effect of Glucose onompAmRNA Stability: a Potential Role of Cyclic AMP in the Repression ofhfqin Escherichia coli

Abstract: Glucose is a carbon source that is capable of modulating the level of cyclic AMP (cAMP)-regulated genes. In the present study, we found that the stability of ompA mRNA was reduced in Escherichia coli when glucose (40 mM) was present in Luria-Bertani (LB) medium. This effect was associated with a low level of cAMP induced by the glucose. The results were confirmed with an adenylyl cyclase mutant with low levels of cAMP that are not modulated by glucose. Northern blot and Western blot analyses revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 38 publications
1
29
0
1
Order By: Relevance
“…However, the studies do appear to affirm a central role of cAMP and the cAMP receptor protein (CRP) in modulation (41) of known (22) and putative (42) virulence genes, including genes involved in flagellar biosynthesis (7), whose expression is known to be under the control of crp (43). Interestingly, the crp gene is itself negatively autoregulated by the cAMP-CRP complex (44).…”
Section: Figmentioning
confidence: 99%
“…However, the studies do appear to affirm a central role of cAMP and the cAMP receptor protein (CRP) in modulation (41) of known (22) and putative (42) virulence genes, including genes involved in flagellar biosynthesis (7), whose expression is known to be under the control of crp (43). Interestingly, the crp gene is itself negatively autoregulated by the cAMP-CRP complex (44).…”
Section: Figmentioning
confidence: 99%
“…Northern blot analysis was performed with 10 lg of total RNA according to the standard protocol as previously described [9]. Briefly, RNA isolation was performed according to the procedures of the TRI reagent-RNA kit (Molecular Research Center, Cincinnati, OH).…”
Section: Cell Growthmentioning
confidence: 99%
“…The membrane was then hybridized with digoxigenin (DIG)-labeled DNA probes for at least 12 h at 42°C. DNA probes specific to E. coli fumA were amplified with dNTPs and DIG-11-dUTP mixture (Roche Applied Science, Mannheim, Germany) similar to that previously described [9]. After hybridization, the membranes were washed and were detected using a chemiluminescent substrate (Roche Applied Science, Indianapolis, IN).…”
Section: Cell Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA chaperone protein Hfq, coupled with three small RNAs (DsrA, RprA, and ArcZ), positively controls rpoS mRNA stability and stimulates translation by facilitating annealing between the small RNAs and the 5= untranslated region (UTR) of the mRNA to open the hairpin (19). Previous research has shown that the expression of hfq is repressed by cAMP-CRP and that glucose is capable of increasing Hfq protein levels through reduction of cAMP levels (40). Therefore, it is justifiable to speculate that cAMP-CRP suppresses rpoS indirectly by repressing hfq expression and then interfering with rpoS mRNA stability.…”
Section: Discussionmentioning
confidence: 99%